Internal Control, Organizational Culture, and Leadership Style: Analysis of the Impact on Employee Fraud - Fernaldy, Victorio Yosafat; Susilawati, Clara (Jurnal Akuntansi, 2024)
Purpose - This study focuses on manufacturing companies as its subjects of investigation. Its primary objective is to find out the impact of internal control mechanisms, organizational culture, and leadership styles on incidences of employee fraud within manufacturing firms in Semarang City. Design/methodology/approach - This research uses quantitative methods, utilizing primary data gathered through a structured questionnaire. The study encompasses all employees across 515 manufacturing companies in Semarang City, with a sample size of 90 selected through purposive sampling techniques. Data related to these manufacturing entities was sourced from the Central Statistics Agency of Semarang City. Statistical analysis was conducted using multiple regression techniques aided by SPSS software. Finding - The results showed that leadership style had a significant effect on employee fraud. Meanwhile, internal control and organizational culture have no influence on employee fraud. Research limitations/implications – Some companies did not give permission to conduct the research at their company and it is difficult to get respondents who fit the criteria. The future researchers are suggested to add respondents’ number used as research material. Keywords: Internal Control, Organizational Culture, Leadership Style, Employee Fraud, Manufacturing Company